Designing Iran's National Branding Model through the Sport Industry - Mahboubeh Khodaparast (Archives in Sport Management and Leadership)
The main goal of the current research was to design a national branding model of Iran through the sport industry. This research was conducted using Grounded theory qualitative method. The statistical population of the research included specialists and experts familiar with the topic of branding, global marketing in sport and related issues, as well as those involved in the country's sport; who were selected using theoretical and snowball sampling methods and their number reached 18 people. The tool and method of data collection was an individual semi-structured interview. In order to analyze the data, Glazeri's approach was used, including three main steps of open coding, selective coding and theoretical coding. During the process of open and selective coding, a total of 134 concepts and 11 main categories were identified. The obtained categories were divided into 2 general dimensions "factors affecting national branding through the sport industry" (6 categories, 93 concepts) and "Consequences of national branding of Iran through the sport industry" (5 categories, 41 concepts). In the theoretical coding stage, the final research model was drawn. Knowing the factors affecting the national branding of the country and its wide consequences, aligning the attitude-behavior of the country's managers and sport and non-sport officials is necessary to move in this direction.